You have to set up a proportion so 2 over 3= x over 60. So multiply 2 times 60= 120 divided by 3 which is 40
Answer:
we have:
8x³ + mx² - 6x + n
= 8x³ - 8x² + (m + 8)x²- (m + 8)x + (m + 2)x - (m + 2) + m + 2+ n
= 8x²(x - 1) + (m + 8)x(x - 1) + (m + 2)(x - 1) + (m + n + 2)
= (x - 1)[8x² + (m + 8)x + m + 2] + (m + n + 2)
because the remainder if divided by (x-1) is 2
=> m + n + 2 = 2
⇔ m + n = 0 (1)
we also have:
8x³ + mx² - 6x + n
= 8x³ - 12x² + (m + 12)x² - 3/2.x.(m + 12) + ( 12 + 3/2.m)x - (9/4.m + 18) + n +9/4m + 18
= 4x²(2x - 3) + 1/2.(m + 12)x(2x - 3) + (3/2m + 12).1/2.(2x - 3) + 9/4m + n + 18
= (2x - 3)(4x² + (m + 12)/2.x + 3/4m + 6) + 9/4m + n + 18
because the remainder if divided by (2x - 3) is 8
=> 9/4m + n + 18 = 8
⇔ 9/4m + n = -10 (2)
from (1) and (2), we have:
m + n = 0
9/4m + n = -10
=> m = -8
n = 8
Step-by-step explanation:
Answer:
26.875 = 26.88
86km = 60 minutes
86km/2=
43
43/1.6(kilometers in miles)
26.88
hope this helps uwu
Answer:
20 is the answer
Step-by-step explanation:
10× 2× 1 = 20
Answer:
62 ft²
Step-by-step explanation:
l = 3
w = 2
h = 5
now
2(wl+hl+hw)
2(2×3+5×3+5×2)
2×31
62 ft²